S85 Leucine-rich 2 glycoprotein-1 upregulation in plasma of patients with active tuberculosis. (11th November 2022) - Kutschenreuter, J; Loader, MC; Kirwan, DE; Gilman, RH; Friedland, JS; Chong, DLW
Abstract : Background: Tuberculosis (TB) is responsible for more than 1.2 million deaths annually. Neutrophils have a central role in driving both morbidity and mortality in patients, but the exact mechanisms involved remain unclear. Leucine-rich 2 glycoprotein-1 (LRG1) was proposed as a novel biomarker for active TB, but its cellular source and role in TB pathogenesis in patients are unknown. We investigated whether neutrophils are key regulators of LRG1 secretion during TB. Methods: Serum LRG1 was measured by ELISA in a cohort of Peruvian TB patients ( n =64, healthy controls n =51) at diagnosis and after 45 days of treatment. LRG1 expression was assessed in lymph node biopsies from patients with TB. For cellular studies, human peripheral neutrophils from healthy donors were infected for 4 h with Mycobacterium tuberculosis ( Mtb) at a multiplicity of infection of 1 or stimulated with conditioned media from Mtb -infected monocytes (CoMTb). CoMTb was also used to stimulate primary human bronchial epithelial cells. Secreted LRG1 concentrations were quantified by ELISA. Results: We found significantly increased serum LRG1 concentrations in TB patients compared to healthy controls (61.6±34.8 vs. 20.5±14.1 µg/ml resp., p <0.0001), which decreased significantly after 45 days of anti-mycobacterial treatment (mean difference = -37.06±5.7 µg/ml, p <0.0001) in patients with drug-sensitive disease. Addtionally, LRG1 was detected in granulomas in lymph node tissue from TB patients by immunohistochemistry. Neutrophils from healthy donors infected with Mtb in vitro secreted significant amounts of LRG1 compared to uninfected controls (1.3 vs. 0.24 ng/ml, p =0.0159). Similarly, stimulation with CoMTb resulted in significant increase in LRG1 secretion compared to control-stimulated neutrophils (2.23 vs. 0.53 ng/ml, p =0.0121) and bronchial epithelial cells (2.1 vs. 0.7 ng/ml, p =0.0003). Conclusion: We confirm that serum LRG1 concentrations are elevated in TB patients and decrease significantly during anti-mycobacterial therapy. We have also identified two cellular sources of LRG1 in TB infection: neutrophils and bronchial epithelial cells, which secrete LRG1 during direct Mtb infection or in a monocyte-dependent network of TB infection. This indicates, that those cell types may be key secretors of LRG1 in TB disease. Moreover, serum LRG1 concentrations represents a clinical biomarker of active TB disease.